PENGGUNAAN MEDIA BUKA KOTAK PADA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS IV SDN 6 PADANG SIBUSUK KECAMATAN KUPITAN KABUPATEN SIJUNJUNG - Rinawanti Rinawanti (JOURNAL OF COMMUNITY DEDICATION, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) of fourth grade students of SDN 6 Padang Sibusuk, Kupitan District, Sijunjung Regency, by utilizing Word Wall media through the "Buka Kotak" method. The background of this study is the low learning outcomes of students in the PAI subject due to the use of conventional learning methods that are less interactive. Word Wall media was chosen because it has various interactive features that can increase student interest and participation in learning. This study uses a Classroom Action Research (CAR) approach which is implemented in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. In cycle I, learning activities showed quite good results with an average student score of 76 and a classical completion rate of 70%. However, there were several obstacles such as lack of student motivation and technical limitations in the use of media. To overcome these obstacles, improvements were made in cycle II, including improving the quality of the media used and providing additional motivation to students. The results in cycle II showed a significant increase with an average student score of 83 and classical completion increasing to 90%. In addition, students gave positive responses to the use of Word Wall media, which was considered interesting, interactive, and made it easier to understand Islamic Religious Education material. This study concluded that the use of Word Wall media was effective in improving students' Islamic Religious Education learning outcomes. In addition to providing a positive impact on learning outcomes, this media also increases student participation and motivation in learning. Thus, the use of technology-based learning media such as Word Wall can be an innovative and relevant alternative to support the learning process, especially in Islamic Religious Education subjects.